Synaptobrevin Transmembrane Domain Dimerization Studied by Multiscale Molecular Dynamics Simulations - Han, Jing; Pluhackova, Kristyna; Wassenaar, Tsjerk; Böckmann, Rainer (Biophysical Journal, 2015)
Synaptic vesicle fusion requires assembly of the SNARE complex composed of SNAP-25, syntaxin-1, and synaptobrevin-2 (sybII) proteins. The SNARE proteins found in vesicle membranes have previously been shown to dimerize via transmembrane (TM) domain interactions. While syntaxin homodimerization is supposed to promote the transition from hemifusion to complete fusion, the role of synaptobrevin's TM domain association in the fusion process remains poorly understood. Here, we combined coarse-grained and atomistic simulations to model the homodimerization of the sybII transmembrane domain and of selected TM mutants. The wild-type helix is shown to form a stable, right-handed dimer with the most populated helix-helix interface, including key residues predicted in a previous mutagenesis study. In addition, two alternative binding interfaces were discovered, which are essential to explain the experimentally observed higher-order oligomerization of sybII. In contrast, only one dimerization interface was found for a fusion-inactive poly-Leu mutant. Moreover, the association kinetics found for this mutant is lower as compared to the wild-type. These differences in dimerization between the wild-type and the poly-Leu mutant are suggested to be responsible for the reported differences in fusogenic activity between these peptides. This study provides molecular insight into the role of TM sequence specificity for peptide aggregation in membranes.